SOSIALISASI PENYELENGGARAAN JENAZAH BAGI JAMAAH MASJID NURUL FALAH BERDASARKAN PUTUSAN TARJIH MUHAMMADIYAH - Romi Saputra; Firdaus Firdaus; Desminar Desminar; Khoiriah Khoiriah; Andi Irawan; Sri Rahayu Nengsih (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
The decision of the Tarjih Muhammadiyah Assembly in various aspects to date has not been socialized to the wider community properly, so how the decision of the Muhammadiyah tarjih assembly is not actualized in people's lives, without exception related to the implementation of bodies. This activity is designed in the form of socialization, to facilitate the achievement of the purpose of this activity involves lecturers and students of the Faculty of Islamic Religion and the target community is the congregation nurul Falah Mosque. The results of this activity was declared valuable because it was seen that the understanding of nurul falah mosque worshippers is increasing in practicing the decision of the tarjih assembly in the field of proper implementation of the body, this conclusion is based on the ability of the pilgrims in practicing the implementation of the body ranging from facing the sacratul death, arranging the position of the corpse before the implementation of fardhu kifayah, bathing the body, praying, smoothing up to mengkafani. The results of the activities were proven by the cognitive ability of the target object that they obtained through socialization in the form of the dissemination of sheets containing materials and lectures, as well as their practical abilities obtained through demonstrations.